2021
DOI: 10.3390/cancers13246170
|View full text |Cite
|
Sign up to set email alerts
|

The Vulvar Cancer Risk in Differentiated Vulvar Intraepithelial Neoplasia: A Systematic Review

Abstract: Differentiated vulvar intraepithelial neoplasia (dVIN) is the precursor of human papillomavirus (HPV)-independent vulvar squamous cell carcinoma (VSCC). Given the rare incidence of dVIN, limited information on the exact cancer risk is available. We systematically reviewed the primary and recurrent VSCC risk in patients with dVIN, as well as the time to cancer development. A systematic search was performed up to July 2021 according to the PRISMA guidelines. Five reviewers independently screened articles on titl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 32 publications
(80 reference statements)
2
22
0
Order By: Relevance
“…Unfortunately, the clinical behavior of these lesions is unknown. However, the appropriate classification of these lesions as HPV-independent might be clinically relevant in similarity with HPV-independent squamous premalignant lesions of the vulva which have proven to be more aggressive in the vulva 36. Thus, the patients with HSIL-like HPV-independent lesions of the penis will probably have to undergo a stricter follow-up than patients with penile HSIL.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the clinical behavior of these lesions is unknown. However, the appropriate classification of these lesions as HPV-independent might be clinically relevant in similarity with HPV-independent squamous premalignant lesions of the vulva which have proven to be more aggressive in the vulva 36. Thus, the patients with HSIL-like HPV-independent lesions of the penis will probably have to undergo a stricter follow-up than patients with penile HSIL.…”
Section: Discussionmentioning
confidence: 99%
“…If untreated, dVIN will progress to squamous cell carcinoma (SCC) more often than HSIL (50% versus 5.7%) [ 30 , 31 ]. The absolute risk for primary VSCC in dVIN varies between 33% and 86%, with the median time for progression of 9–23 months [ 32 ].…”
Section: Specific Features Of Vulvar Intraepithelial Neoplasiamentioning
confidence: 99%
“…Most markers showed significantly higher methylation levels in dVIN compared to vHSIL, which is consistent with the higher cancer risk in patients with dVIN. 6,7 Interestingly, a more heterogeneous methylation pattern was observed within the vHSIL group, likely reflecting a varying cancer risk. A previous study by our research group also identified SST as one of the best-performing methylation markers for cancer risk stratification in HPV-induced anal lesions.…”
Section: Discussionmentioning
confidence: 97%
“…[4][5][6] Patients with vHSIL and HPV-independent VIN have a varying risk of developing cancer, with a 10-year cumulative VSCC risk of 10% vs 50%, respectively. 6,7 Due to this risk, patients with vHSIL and HPV-independent VIN frequently undergo surgical interventions resulting in physical and psychosexual morbidity. 8 However, as only a minority of vHSIL patients develop cancer, prognostic biomarkers reflecting the cancer risk could reduce the necessity for mutilating overtreatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation